Insight Into the Role of PC71BM on Enhancing the Photovoltaic Performance of Ternary Organic Solar Cells - Wang, Bei; Fu, Yingying; Yan, Chi; Zhang, Rui; Yang, Qingqing; Han, Yanchun; Xie, Zhiyuan (Frontiers in Chemistry, 2018)
The development of non-fullerene acceptor molecules have remarkably boosted power conversion efficiency (PCE) of polymer solar cells (PSCs) due to the improved spectral coverage and reduced energy loss. An introduction of fullerene molecules into the non-fullerene acceptor-based blend may further improve the photovoltaic performance of the resultant ternary PSCs. However, the underlying mechanism is still debatable. Herein, the ternary PSCs based on PBDB-T:ITIC:PC71BM blend were fabricated and its PCE was increased to 10.2% compared to 9.2% for the binary PBDB-T:ITIC devices and 8.1% for the PBDB-T:PC71BM PSCs. Systematic investigation was carried out to disclose the effect of PC71BM on the blend morphology and charge transport behavior. It is found that the PC71BM tends to intermix with the PBDB-T donor compared to the ITIC counterpart. A small amount of PC71BM in the ternary blend is helpful for ITIC to aggregate and form efficient electron-transport pathways. Accordingly, the electron mobility is increased and the density of electron traps is decreased in the ternary blend in comparison with the PBDB-T:ITIC blend. Finally, the suppressed bimolecular recombination and enhanced charge collection lead to high PCE for the ternary solar cells.